2003
DOI: 10.1071/ar02156
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex, and weight at weaning influence organ weight and gastrointestinal development of weanling pigs

Abstract: The present study was designed to determine the interrelationships between sex, weaning age, and weaning weight on aspects of physiological and gastrointestinal development in pigs. Forty-eight Large White × Landrace pigs were used in a factorial arrangement with the respective factors being: age at weaning (14 or 28 days), weight at weaning (heavy or light), sex (boar or gilt), and time after weaning (1, 7, and 14 days). At weaning, 48 pigs were removed from the sow: 16 pigs were then fasted for 24 h before e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 30 publications
(45 reference statements)
3
40
0
2
Order By: Relevance
“…The influence of fibre level and fibre source in the diet on the development of the visceral organs and GIT of growing pigs in general and of piglets in particular has been documented in a number of reports which showed that pigs fed high‐fibre diets had heavier weight of GIT than those given a low‐fibre diet (Jørgensen et al.,1996a; Nyachoti et al., 2000; Freire et al., 2003; Pluske et al., 2003) which is in agreement with the results of the present study. However, the effect varied between fibre sources because of the different fibre components, for example, the ratio of soluble/insoluble fibre (Bach Knudsen and Jørgensen, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The influence of fibre level and fibre source in the diet on the development of the visceral organs and GIT of growing pigs in general and of piglets in particular has been documented in a number of reports which showed that pigs fed high‐fibre diets had heavier weight of GIT than those given a low‐fibre diet (Jørgensen et al.,1996a; Nyachoti et al., 2000; Freire et al., 2003; Pluske et al., 2003) which is in agreement with the results of the present study. However, the effect varied between fibre sources because of the different fibre components, for example, the ratio of soluble/insoluble fibre (Bach Knudsen and Jørgensen, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the absolute weight of visceral organs and GIT increased with piglet age. However, when expressed as g/kg EBW, the weight of visceral organs decreased with age, which is in agreement with Pluske et al. (2003), who found that the relative weight of the visceral organs of piglets had a tendency to decrease between 14 and 28 days of age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All components and accessory organs of the GIT are influenced by weaning, irrespective largely of weaning age; however, because of its size and biological importance, it is the small intestine that is affected the most and has to make the greatest anatomical, physiological, and immunological adaptation to changes in the pattern and form of feed consumption, changes in dietary substrates, and adjustment to stress (e.g., Stokes et al, 1994;Cranwell, 1995;Xu, 1996;Pluske et al, 1997;Zabielski et al, 1999;Burrin and Stoll, 2003;Pluske et al, 2003;Boudry et al, 2004;Lallès et al, 2004;Burkey et al, 2009;Wijtten et al, 2011Wijtten et al, , 2012Pluske, 2013). It is simply beyond the scope of this review to summarize all the changes to the GIT that occur in the periweaning period, with a plethora of authors having already described the rapid and consistent changes to structure (e.g., villous height and crypt depth, size and shape, tight junction integrity) and function (e.g., digestive and absorptive activity and capacity, loss of surface area, inflammation, antioxidant capacity) that occur in the acute and adaptive phases of growth in the periweaning period (Fig.…”
Section: Changes To the Structure And Function Of The Git After Weaningmentioning
confidence: 99%
“…Although pulse protein can replace specialty protein feedstuffs in diets for weaned pigs, digestion of protein in raw field pea might be a concern for pigs immediately after weaning due to a less-developed digestive system (Pluske et al, 2003;Lalles et al, 2007;Gunawardena et al, 2010b). The storage protein in field pea is mainly globulin, e.g., legumin and vicilin (Boulter, 1983).…”
Section: Discussionmentioning
confidence: 99%